Merits and demerits of selective isolation of superspreaders: A mathematical modeling study based upon West Bengal (India) SARS-COV 2 data - Sourodip Ghoshdastidar; Kamalesh Sarkar; Biswajit Ghoshdastidar (Wolters Kluwer Medknow Publications, 2021)
Context: All COVID cases and their contacts are considered highly infectious requiring isolation, which blocks the COVID isolation beds and disrupts life in the community. Aim: To find out the effect of selective isolation and contact tracing of superspreaders as compared with the conventional ongoing protocol. Settings and Design: A mathematical model was designed to look at the effect of isolation and contact tracing of only those with high viral loads (superspreaders) on COVID-19 bed occupancy and overall mortality, in comparison with conventional protocol of isolation and contact tracing of all cases. Materials and Methods: An agent-based model, calibrated to the ongoing West Bengal COVID-19 data, was run for a total of 178 days to find out the effect of the interventions on COVID-19 bed occupancy and mortality. Results: There is an impressive reduction in the occupancy of COVID isolation beds, even with the preintervention testing rate with no negative impact on mortality. Conclusions: Strict isolation of superspreaders only, maybe highly effective in reducing the burden on health care and solving the COVID isolation bed crises if the testing rate is significantly increased.